2011
DOI: 10.5588/ijtld.10.0403
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping and drug resistance patterns of Mycobacterium tuberculosis strains in five provinces of China

Abstract: The M. tuberculosis Beijing genotype varies in prevalence in different regions of China and is solely associated with RMP resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 0 publications
2
16
0
Order By: Relevance
“…This result is similar to the two previous large-scale studies conducted in China [9], [10]. Dong et al analyzed 2,346 M. tuberculosis isolates from 13 provinces and showed that Beijing family isolates were prevalent all over the country (74.08%) [9], while Guo et al reported that 77.8% of 158 strains isolated in five provinces belonged to the Beijing genotype [10]. However, this rate was much lower (62.2%) in a recent study of 4017 isolates from the National Drug Resistance Base-Line Surveillance of Tuberculosis [11].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This result is similar to the two previous large-scale studies conducted in China [9], [10]. Dong et al analyzed 2,346 M. tuberculosis isolates from 13 provinces and showed that Beijing family isolates were prevalent all over the country (74.08%) [9], while Guo et al reported that 77.8% of 158 strains isolated in five provinces belonged to the Beijing genotype [10]. However, this rate was much lower (62.2%) in a recent study of 4017 isolates from the National Drug Resistance Base-Line Surveillance of Tuberculosis [11].…”
Section: Discussionsupporting
confidence: 92%
“…Our study found that the Beijing family strains were prevalent in the total collection (79.5%). This result is similar to the two previous large-scale studies conducted in China [9], [10]. Dong et al analyzed 2,346 M. tuberculosis isolates from 13 provinces and showed that Beijing family isolates were prevalent all over the country (74.08%) [9], while Guo et al reported that 77.8% of 158 strains isolated in five provinces belonged to the Beijing genotype [10].…”
Section: Discussionsupporting
confidence: 86%
“…Particular M. tuberculosis genotypes have been found to be related to the risk of transmission. Previous studies [6], [16][18] have described the distribution of various genotypes of TB strains from many areas in China. However, a detailed analysis of the population structure of TB strains from the metropolitan area of Beijing, one of the largest cities in the world, with a high prevalence of TB, has not been conducted.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in accordance with data from previous studies using MIRU-VNTR typing for genotyping of strain collections comprising a higher proportion of Beijing strains. It has already been shown that 12-loci MIRU-VNTR typing was not sufficient to discriminate Beijing family strains (6,9). Similarly, Hanekom and colleagues reported that even 15-and 24-loci MIRU-VNTR typing has a reduced discriminatory power compared to IS6110 typing for strains of the Beijing lineage in Cape Town, South Africa, and that the inclusion of more variable loci might be necessary to reach the same level as that with IS6110 RFLP typing (7).…”
Section: Discussionmentioning
confidence: 99%
“…In comparative populationbased evaluations, we and others found a similar if not slightly better performance of 15-or 24-loci MIRU-VNTR typing compared to IS6110 RFLP typing for discrimination of clinical isolates and detection of transmission chains in TB patient populations (13). Few subsequent studies compared MIRU-VNTR typing with the "gold standard" IS6110 RFLP typing, because the latter is rather laborious and more difficult to perform (6,7,15). The majority of the studies confirmed the initial finding that 24-loci MIRU typing can be used for MTBC genotyping with a similar performance as IS6110 typing, but some studies suggested a lower discriminatory power of 24-loci MIRU-VNTR typing in settings where Beijing strains are dominant (7,15).…”
Section: Discussionmentioning
confidence: 99%